A history of the modern world - Palmer, R. R. (Robert Roswell), 1909-2002.; Colton, Joel, 1918-2011. (New York : McGraw-Hill, 1995)
The extraordinary events of the last few years have made this eighth edition come sooner than usual after its predecessor. It is of course too early to assess the magnitude and consequences of what has happened, but we have done much new writing, rewriting, rewording, and rearrangement to present the upheavals in Eastern Europe, the disintegration fo the former Soviet Union, the reunification of Germany, the end of the Cold War, the Islamic fundamentalist movement, changes in latin america, and much else.
Plebeian uprisings in France preceding the Fronde, 1623-1648 / by B.F. Porshnev -- The English Revolution, 1640-1660 / by Perez Zagorin -- The English Revolution and the brotherhood of man / by Christopher Hill -- Emergence of the concept of revolution / by Karl Griewank -- The world revolution of the West, 1763-1801 / by R.R. Palmer -- The French Revolution in the context of world history / by Georges Lefebvre -- The revolution of 1848 / by Henri Brunschwig -- Russia and 1848 / by Isaiah Berlin -- The background of the Russian Revolution / by E.H. Carr -- The Bolsheviks and their rivals / by Leonard Schapiro -- The Russian Revolution runs its course / by Robert V. Daniels.
Includes bibliographical references (pages 1106-1225) and index.
Keywords: History, Modern; Histoire moderne et contemporaine; History, Modern; Wereldgeschiedenis